Explanation in biology - Ross, Lauren N. (Cambridge elements. Elements in the philosophy of biology, 2024)
This Element examines philosophical accounts of scientific explanation, particularly those that apply to biology and the life sciences. Two main categories of scientific explanation are examined in detail -causal explanations and non-causal explanations. The first section of this Element provides a brief history and some basics on philosophical accounts of scientific explanation. Section 2 covers causal explanation, first by discussing foundational topics in the area, such as defining causation, causal selection, and reductive explanation. This is followed by an examination of distinct types of causal explanation, including those that appeal to mechanisms pathways, and cascades. The third section covers non-causal, mathematical explanations, which have received significant attention in philosophy of biology and the life sciences. Three main types of non-causal, mathematical explanation are discussed: topological and constraint-based explanation, optimality and efficiency explanations, and minimal model explanations. This title is also available as Open Access on Cambridge Core.